Interpersonal discrimination and self-rated health among sexual and gender minority employees: the moderating role of allyship - Bjerkestrand, Lukas H.; Stabbetorp, Tine M.; Bye, Hege H. (Frontiers in Organizational Psychology, 2025)
IntroductionSexual and gender minorities (SGMs) are more often targets of negative interpersonal behaviors at work and as a result report worse health than their cisgender and heterosexual coworkers. We argue that by engaging in acts of allyship—such as defending and empowering SGMs—employees can contribute to better the health of SGMs in the workplace. Specifically, we hypothesized that there are negative associations between observing and experiencing interpersonal discrimination and self-rated health, and that these can be moderated by experiencing and observing SGM allyship.MethodsWe tested these hypotheses in a large sample of Norwegian SGMs (N = 438) originally recruited for the Sexual Orientation, Gender Diversity, and Living Conditions Study.ResultsBoth experiencing (r = −0.15, p < 0.001) and observing interpersonal discrimination (r = −0.21, p < 0.001) were significantly related to poorer self-rated health. As expected, regression analyses showed that experiencing allyship moderated the association between experiencing interpersonal discrimination and self-rated health (b = 0.26, p = 0.046, 95% CI [0.004, 0.520]). Experiencing allyship also moderated the negative effect of observing interpersonal discrimination on self-rated health (b = 0.21, p = 0.028, 95% CI [0.023, 0.391]). The difference in self-rated health between individuals who had experienced or observed interpersonal discrimination and those who had not was substantially reduced at higher levels of experienced allyship. Contrary to our hypotheses, observing allyship was not a significant moderator.DiscussionThe findings extend previous research on the benefits of allyship for SGM employees and have implications for the promotion of SGMs' wellbeing at work.